Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 1 - Equations and Inequalities - 1.3 Complex Numbers - 1.3 Exercises - Page 112: 56



Work Step by Step

$(-2+3i)(4-2i)$ Evaluate the product by multiplying each term of the first factor by every term of the second factor: $(-2+3i)(4-2i)=-8+4i+12i-6i^{2}=...$ Substitute $i^{2}$ by $-1$ and simplify: $...=-8+4i+12i-6(-1)=-8+16i+6=-2+16i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.